Structural performance of precast non-load bearing wall panels with recycled concrete aggregate and perlite - Amir Khomeiny Ruslan,; Noorsuhada Md Nor,; Nur Amira Wahida Musnazri,; Amril Hadri Jamaludin,; Soffian Noor Mat Saliah,; Mohd Azrizal Fauzi,; Ahmad Syauqi Md Hassan,; Nor Azian Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The scarcity of natural sand in wall construction poses a significant challenge, prompting a novel solution in this study: wall panels using Recycled Concrete Aggregates (RCA) and perlite. The lack of existing literature on such panels underscores the study’s importance. Panels of varying thicknesses (75 mm, 100 mm, and 125 mm) are prepared with a 1:4 concrete mix, with the aggregate portion consisting of 40% sand, 40% RCA, and 20% perlite. For control purposes, additional wall panels are prepared using natural sand as the aggregate. Subsequently, all panels undergo compressive tests to evaluate their structural performance, including crack analysis. Comprehensive analyses, encompassing load, stress, and strain, yield Young’s Modulus and Poisson’s Ratio. Strain gauges and acoustic emissions enhance data precision. Maximum loads of 936.51 kN are observed on 125 mm panels. Findings reveal variations in compressive strength, with control panels surpassing the proposed ones. Wall panel thickness proves pivotal, influencing both strength and crack visibility. Notably, the 100 mm panel performs optimally, displaying minimal percentage differences in compressive strength compared to the control. This research offers invaluable insights into alternative aggregate-infused wall panels’ structural behaviour, enriched by verification through an AE analysis.